Understanding Microservices Architecture: A Comprehensive Guide - Surya Prabha Busi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Microservices architecture has emerged as a transformative approach to building complex software systems, offering organizations a way to develop and maintain large-scale applications more effectively. This comprehensive article explores the fundamental concepts, benefits, implementation strategies, and challenges of microservices architecture. The article examines how microservices enable organizations to break down complex applications into manageable, independent services that communicate through well-defined APIs. It delves into the architectural principles that guide successful microservices implementation, including service design, infrastructure requirements, and communication patterns. The article encompasses crucial aspects such as technical agility, independent deployment capabilities, and scalability benefits while addressing critical challenges like distributed system complexity, data consistency, and service boundary definition. Through detailed analysis of industry practices and architectural patterns, this article provides insights into how organizations can leverage microservices to build more resilient, maintainable, and scalable systems while fostering team autonomy and technological flexibility.